AIDS e doenças oportunistas transmissíveis na faixa de fronteira Brasileira AIDS and transmissible opportunistic diseases in the Brazilian border area - Antonio Luiz Rodrigues-Júnior; Euclides Ayres de Castilho (Revista da Sociedade Brasileira de Medicina Tropical, 2010)
INTRODUÇÃO: A transmissão do HIV e de outras doenças transmissíveis, de pessoa a pessoa, pode ser associada à mobilidade humana. Este trabalho avaliou a incidência de doenças oportunistas transmissíveis entre os casos de AIDS, nos municípios da faixa de fronteira brasileira. MÉTODOS: Os municípios da faixa de fronteira brasileira foram agrupados em três regiões culturais; foram consideradas as notificações feitas ao Ministério da Saúde, entre 1990 e 2003, que tenham sido feitas com os critérios de definição CDC adaptado, Rio de Janeiro/Caracas e óbito; as doenças oportunistas detectadas foram agrupadas de acordo com o tipo de transmissão: 1) inalação do agente; 2) ingestão de água/alimento contaminado e 3) contato interpessoal. A análise descritiva considerou regiões culturais, anos de escolaridade, categoria de transmissão, sexo e faixa etária. RESULTADOS: Houve diferentes padrões de incidência de AIDS nos grupos de doenças oportunistas em cada região cultural. A região extremo-sul apresentou a maior incidência de AIDS; o número de casos de AIDS do sexo feminino foi maior na categoria heterossexual; o número de casos de AIDS do sexo masculino foi maior entre usuários de drogas injetáveis; as doenças transmitidas pelo contato interpessoal foram as mais frequentes, destacando a incidência de monilíases; a tuberculose e a pneumonia foram as mais frequentes dentre as doenças transmitidas pela inalação do agente; as doenças transmitidas pela ingestão de água/alimentos contaminados mostraram um padrão de incidência estável. CONCLUSÕES: A fronteira brasileira é um espaço geográfico importante e heterogêneo; o enfrentamento da AIDS deve reconhecer as diferentes geografias culturais. INTRODUCTION: Person-to-person transmission of HIV and other communicable diseases may be associated with human geographic mobility. This article evaluated the incidence of transmissible opportunistic diseases among AIDS cases that had been reported by municipalities in the Brazilian border area. METHODS: Brazilian border area municipalities were grouped into three cultural regions; the source data was AIDS cases registered with the Ministry of Health from 1990 to 2003, which were classified according to CDC-adapted, Rio de Janeiro/Caracas and death criteria; detected communicable opportunistic diseases were categorized into groups according to transmission: 1) inhalation agent; 2) contaminated water and/or food ingestion, and 3) interpersonal contact. The descriptive evaluation considered cultural region, years of schooling, sex and age group. RESULTS: Different AIDS incidence patterns were observed among groups of opportunistic diseases in each cultural region. The extreme southern region showed the greatest incidence of AIDS; the absolute incidence of female cases was greatest in the category of heterosexual transmission; the number of male cases was greatest among intravenous drug users; transmission was most frequent in the interpersonal contact group, particularly incidences of candidiasis; tuberculoses and pneumonias were most frequent in the inhalation agent transmission group; the contaminated water/food ingestion transmission group showed an unchanged pattern of absolute incidence. CONCLUSIONS: The Brazilian border area is a very important and heterogeneous geographic phenomenon; AIDS programs must recognize different cultural geographies.